Staphylococcus aureus enterotoxin A gene induce the changes in the expression of apoptosis-related genes in AGS cell line - Afzali, Sara; Doosti, Abbas; Heidari, Mansour; Babaei, Nahid; Keshavarz , Parvaneh (Journal of BioScience and Biotechnology, 2021)
Gastric cancer is one of the most common malignancies worldwide and it is the fourth leading cause of cancer-related death. Staphylococcus aureus enterotoxin A (SEA) is one of the toxins affecting the expression of apoptotic-related genes. The aim of this research is to investigate the effects of S. aureus enterotoxin A on the expression of BAK, FAS, BAX, TNF-α, BCL-2 and Survivin in AGS cell lines. In this study, AGS cells were transfected with the pcDNA3.1(+)-enterotoxin A or empty pcDNA3.1(+) plasmids using Lipofectamine 2000. The cells were grown in Dulbecco’s modified Eagle’s medium (DMEM) with 10% FBS. Then, the mRNA expression level of BAK, FAS, BAX, TNF-α, BCL-2 and Survivin was measured by qRT-PCR method. Our findings indicated that Staphylococcus aureus enterotoxin A markedly altered the expression level of the apoptotic-related gene of the AGS cell line. The mRNA expression of BAK, FAS, BAX and TNF-α genes increased statistically significant in enterotoxin A treated AGS cells compared with the control group. On the contrary, BCL2 and Survivin mRNA expression showed a significant decrease compared with AGS cells were transformed by empty pcDNA3.1(+) plasmid. We suggested that SEA could represent an agent that can significantly changes apoptosis-related genes expression in AGS cell line, leading to reduction of tumor cell proliferation.